Impacto del tratamiento de datos en la toma de decisiones del gobierno autónomo descentralizado de Quevedo, 2023. - Cedeño Pincay, Francisca Jesús (2025)
The study conducted focused on investigating the issue defined as: What is the influence of data processing on decision-making in the Government Autonomous Decentralized Entity of Quevedo? The main objective of this study was to evaluate the impact of data processing on the effectiveness of decision-making in the Government Autonomous Decentralized Entity of Quevedo during the year 2023. The methodology used descriptive and exploratory research types. The methods employed were both qualitative and quantitative. The techniques used were interviews and surveys. The instrument was a structured questionnaire. The population consisted of one executive and nine technicians from the ICT department and 27,416 citizens of Quevedo (ages 18-79). Regarding the sample, the entire ICT department staff and 379 citizens from the canton of Quevedo were considered. Among the most relevant results, it is described that data processing at the GAD of Quevedo faces significant challenges related to infrastructure, staff knowledge, and organizational culture. The conclusions highlight that there are still areas for improvement in terms of accessibility, clarity, and reliability of the processed information. Optimizing the processes of data collection, analysis, and dissemination is crucial to improving the efficiency and effectiveness of government decisions, which in turn affects citizen satisfaction and well-being.